Alteration of Venous Drainage Route in Idiopathic Normal Pressure Hydrocephalus and Normal Aging - Satow, Takeshi; Aso, Toshihiko; Nishida, Sei; Komuro, Taro; Ueno, Tsukasa; Oishi, Naoya; Nakagami, Yukako; Odagiri, Masashi; Kikuchi, Takayuki; Yoshida, Kazumichi; Ueda, Keita; Kunieda, Takeharu; et al. (Frontiers in Aging Neuroscience, 2017)
Idiopathic normal pressure hydrocephalus (iNPH) is a highly prevalent condition in the elderly population; however, the underlying pathophysiology in relation to the aging process remains unclear. To investigate the effect of removal of cerebrospinal fluid by lumbar “tap test” on the cerebral circulation in iNPH patients, 14 “probable” iNPH patients were studied using a novel blood tracking technique based on blood oxygenation level-dependent (BOLD) magnetic resonance signal intensity. By tracking the propagation of the low-frequency component of the BOLD signal, extended venous drainage times were observed in the periventricular region of iNPH patients, which was reversed by tap test. Interestingly, the venous drainage time in the periventricular region exhibited an age-related prolongation in the healthy control group. Additional regression analysis involving 81 control subjects revealed a dissociation of deep and superficial venous systems with increasing age, presumably reflecting focal inefficiency in the deep system. The overall results not only provide a clue to the etiology, but also suggest a possible noninvasive biomarker for screening iNPH.